Bamboo archway, Trinidad - (:unkn) unknown (My University, 2010)
Bamboo stalks arch over a road somewhere in Trinidad.
Colour: Black and white; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Bamboo--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Roads--Trinidad and Tobago; Women--Trinidad and Tobago